Da Vinci Xi robot-assisted resection of a large caudate lobe liver tumor: Case report and technical discussion - Zhichao Yang; Xinyu Ma; Haitao Yang; Zihao Li; Guangchao Yang; Linqiang Li; Yong Ma (Intelligent Surgery)
Background: This study details the surgical process of using the da Vinci Xi surgical robot to resect a large caudate lobe liver tumor. It aims to share technical experience in robot-assisted resection of large tumors in the caudate lobe of the liver. Objective: To provide evidence supporting the feasibility and safety of robot-assisted liver caudate lobe tumor resection. Methods: On August 5, 2024, the First Affiliated Hospital of Harbin Medical University successfully performed a large caudate lobe tumor resection adjacent to the inferior vena cava using the da Vinci Xi robotic system on a 23-year-old male. Surgical time, techniques, intraoperative blood loss, and postoperative recovery were documented and analyzed. Results: The surgery was successfully completed in 195 ​min with an intraoperative blood loss of 200 ​mL, and no severe postoperative adverse events occurred. The patient recovered well under Enhanced Recovery After Surgery (ERAS) protocols and was discharged. Pathological examination confirmed focal nodular hyperplasia of the liver, with the tumor measuring 8 ​× ​5 ​× ​4.5 ​cm. Conclusion: Robot-assisted liver tumor resection with the da Vinci Xi system is a safe and reliable surgical approach for treating large benign tumors of the liver caudate lobe. This study contributes to the clinical application of such surgeries and further confirms their safety and feasibility.